PENGARUH NILAI TUKAR DAN INVESTASI ASING LANGSUNG TERHADAP UTANG LUAR NEGERI INDONESIA: PENDEKATAN ARDL - Adawiyah, Baiq Rabiatul; Suprapti, Ida Ayu Putri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
Foreign debt plays a crucial role in Indonesia's economy, exchange rate fluctuations and foreign direct investment (FDI) inflows may affect its sustainability. This study examines the extent to which these factors influence Indonesia’s external debt. This study aims to analyze the impact of exchange rates and FDI inflows on Indonesia's foreign debt while evaluating the long- and short-term implications of exchange rate volatility. The study employs the Autoregressive Distributed Lag (ARDL) approach to estimate the relationship between exchange rates, FDI inflows, and Indonesia’s foreign debt over the period 1970–2023. The empirical analysis reveals that a 1 percent depreciation of the rupiah increases foreign debt by 1.28 percent, while a 1 percent increase in FDI inflows raises foreign debt by 11.34 percent, both at a significance level below 5 percent. This study underscores the importance of exchange rate stability in ensuring sustainable external debt management. While FDI serves as an alternative source of capital, excessive reliance on foreign investment heightens external risks. Therefore, strategic economic policies are necessary to maximize the benefits of FDI while mitigating its potential adverse effects on Indonesia's foreign debt.